2018
DOI: 10.3390/medsci6020043
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Systems Biologic Approach in Cell Signaling and Drug Development Responses—A Mini Review

Abstract: The immune system is an integral aspect of the human defense system and is primarily responsible for and involved in the communication between the immune cells. It also plays an important role in the protection of the organism from foreign invaders. Recent studies in the literature have described its role in the process of hematopoiesis, lymphocyte recruitment, T cell subset differentiation and inflammation. However, the specific molecular mechanisms underlying these observations remain elusive, impeding the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Thus, through these systems biologybased studies, novel pharmaceuticals (IDR-1018) and 2 existing drugs (Metformin and salubrinal) were identified as potential treatments for CF-related hyperinflammation. As such, along with numerous other studies [e.g., (89)(90)(91)(92)], it has been shown that integrating omics datasets using resources such as InnateDB and DrugBank can reveal potential drug targets for improved therapies.…”
Section: Drug Discovery and Repurposingmentioning
confidence: 95%
“…Thus, through these systems biologybased studies, novel pharmaceuticals (IDR-1018) and 2 existing drugs (Metformin and salubrinal) were identified as potential treatments for CF-related hyperinflammation. As such, along with numerous other studies [e.g., (89)(90)(91)(92)], it has been shown that integrating omics datasets using resources such as InnateDB and DrugBank can reveal potential drug targets for improved therapies.…”
Section: Drug Discovery and Repurposingmentioning
confidence: 95%